2021
DOI: 10.5194/gmd-14-3683-2021
|View full text |Cite
|
Sign up to set email alerts
|

Modifying emissions scenario projections to account for the effects of COVID-19: protocol for CovidMIP

Abstract: Abstract. Lockdowns to avoid the spread of COVID-19 have created an unprecedented reduction in human emissions. While the country-level scale of emissions changes can be estimated in near real time, the more detailed, gridded emissions estimates that are required to run general circulation models (GCMs) of the climate will take longer to collect. In this paper we use recorded and projected country-and-sector activity levels to modify gridded predictions from the MESSAGE-GLOBIOM SSP2-4.5 scenario. We provide up… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 40 publications
1
65
2
Order By: Relevance
“…Refinements to this simple estimate will need to account for several additional complications. The NOx emission changes have temporal structure (Lamboll et al, 2021), as do the sensitivities of methane to NOx (e.g., Stevenson et al, 2004), and these will interact. In addition, we have ignored any spatial variations in aircraft emissions, but Stevenson and Derwent (2009) found that NOx emissions into cleaner environments had larger effects; there are also likely spatial variations within the large regions we have used for the surface NOx emissions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Refinements to this simple estimate will need to account for several additional complications. The NOx emission changes have temporal structure (Lamboll et al, 2021), as do the sensitivities of methane to NOx (e.g., Stevenson et al, 2004), and these will interact. In addition, we have ignored any spatial variations in aircraft emissions, but Stevenson and Derwent (2009) found that NOx emissions into cleaner environments had larger effects; there are also likely spatial variations within the large regions we have used for the surface NOx emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of nitrogen dioxide (NO2) from satellite instruments and nitrogen monoxide (NO) and NO2 from surface sites show that levels of atmospheric NOx (NO + NO2) dramatically fell globally during 2020 (Bauwens et al, 2020) as COVID-19 lockdowns around the world reduced emissions, mainly from transportation (Venter et al, 2020;Lamboll et al, 2021).…”
Section: Measurements Of Atmospheric Methane and Nitrogen Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the new emission data, the scientific community plans to investigate the co-occurrence of climate anomalies and the COVID-19 impacts on global air quality. To this end, a new climate model inter-comparision project for 2015-2050 with the revised emission scenarios has been proposed (Covid-MIP, Lamboll et al, 2021) under the umbrella of the Detection and Attribution Model Intercomparison Project (DAMIP, Gillett et al, 2016) endorsed by CMIP6. Nine CMIP6 models in the sixth assessment report of the IPCC (IPCC, 2021) use the simple plumes aerosol parameterization MACv2-SP (Fiedler et al,3 J o u r n a l P r e -p r o o f…”
Section: Introductionmentioning
confidence: 99%